Triangular cooperation: Broader, more dynamic and flexible - Geovana Zoccal (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
Triangular cooperation (TriCo) has existed as a cooperation mechanism for about 40 years. The first implicit reference was made to it in 1978 in the United Nations Plan of Action for Promoting and Implementing Technical Cooperation among Developing Countries, the Buenos Aires Plan of Action (BAPA). Reacting to the increased complexity of international development cooperation, and going beyond the North-South divide, TriCo aims to (i) foster relations between DAC donors and emerging economies, (ii) strengthen southern providers' capacity in international cooperation for development and (iii) promote international development. Since 1978, TriCo has become broader, more dynamic and flexible, has increased the number of projects and stakeholders involved, and incorporated different processes and approaches (e.g. South-South-South cooperation), including larger partnership strategies. It is now perceived of as key to the sharing of costs, responsibilities and solutions in the implementation of the 2030 Agenda and the Sustainable Development Goals (SDGs). TriCo was mentioned 73 times in the outcome document of the Second High-level UN Conference on South-South Cooperation (BAPA+40), held in Buenos Aires in March 2019. No longer was it a niche topic. It was afforded significance and broadly discussed in an internationally agreed document, thereby becoming a tool for development dialogue at policy level. fOfficial, verified and comparable data on TriCo are often lacking. Yet, many studies and reports shed light on this mechanism. This Briefing Paper is based on more than 30 in-depth interviews with stakeholders, and on analysis of documents and data. It makes three recommendations on ways to advance TriCo as a cooperation mechanism for all donors, and as a support mechanism for the 2030 Agenda: (1) avoid a 'one-size-fits-all' approach; (2) integrate triangular cooperation into existing practices of development cooperation, e.g. as a component of financial and technical projects; and (3) better connect with the debate around multi-stakeholder partnerships (MSPs), in which stakeholders from at least three different sectors work together through an organised, and long-term engagement.
Keywords: 330; Sustainable Development Goals